Physiological Traits of Dihomo-γ-Linolenic Acid Production of the Engineered Aspergillus oryzae by Comparing Mathematical Models - Antimanon, Sompot; Anantayanon, Jutamas; Wannawilai, Siwaporn; Khongto, Bhimabol; Laoteng, Kobkul (Frontiers in Microbiology, 2020)
Dihomo-gamma-linolenic acid (DGLA; C20:3 n-6) is expected to dominate the functional ingredients market as its role in anti-inflammation and anti-proliferation. The DGLA production by the engineered strain of Aspergillus oryzae with over-expressing Pythium 6-desaturase and 6-elongase genes was investigated by manipulating the nutrient and fermentation regimes. Of the nitrogen sources tested, the maximum biomass and DGLA titers were obtained in the cultures using NaNO3 grown at pH 6.0. For establishing economically feasible process of DGLA production, the cost-effective medium was developed by using cassava starch hydrolysate (CSH) and NaNO3 as carbon and nitrogen sources, respectively. The supplementation with 1% (v/v) mother liquor (ML) into the CSH medium promoted the specific yield of DGLA production (YDGLA/X) comparable to the culture grown in the defined NaNO3 medium, and the DGLA proportion was over 22% in total fatty acid (TFA). Besides, the GLA was also generated at a similar proportion (about 25% in TFA). The mathematic models of the cultures grown in the defined NaNO3 and CSH/ML media were generated, describing that the lipid and DGLA were growth-associated metabolites corresponding to the relevant kinetic parameters of fermentations. The controlled mode of submerged fermentation of the engineered strain was explored for governing the PUFA biosynthesis and lipid-accumulating process in relation to the biomass production. This study provides an informative perspective in the n-6 fatty acid production through physiological manipulation, thus leading to a prospect in viable production of the DGLA-enriched oil by the engineered strain.